Pengaruh Kecerdasan Emosional Terhadap Motivasi Belajar pada Santri Pondok Pesantren - Prayitno, Asyhari Eko; Masluchah, Luluk (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
This study aims to determine whether there is an influence of Emotional Intelligence on Learning Motivation in Santri Pondok Pesantren Nurul Huda Al Manshurin Kediri City. The hypothesis proposed is that there is an influence of Emotional Intelligence on Learning Motivation in Santri Pondok Pesantren Nurul Huda Al Manshurin Kediri City. The sample used in this study was 150 Santri of Nurul Huda Al Manshurin Islamic Boarding School in Kediri City which was taken with Purposive Sampling technique. The independent variable in this study is Emotional Intelligence, while the dependent variable is Learning Motivation, both of which are revealed by using a scale. The analysis used is Spearmen's Rho correlation with the results of rho xy = 0.416 and sig. or p = 0.000 (p>0.01). This means that there is a highly significant positive correlation between the Emotional Intelligence variable and the Learning Motivation variable. The results of hypothesis testing show that there is a highly significant positive correlation between Emotional Intelligence and Learning Motivation in students. The higher the Emotional Intelligence, the higher the Motivation to Learn in students.